Effects of rumen undegradable protein sources on nitrous oxide, methane and ammonia emission from the manure of feedlot-finished cattle - Coelho, Larissa de Melo [UNESP]; Brito, Liziane de Figueiredo [UNESP]; Messana, Juliana Duarte [UNESP]; Cardoso, Abmael da Silva [UNESP]; Carvalho, Geovany Macêdo [UNESP]; Torres, Rodrigo de Nazaré Santos [UNESP]; Carlos, Roberta Souto [UNESP]; Malheiros, Euclides Braga [UNESP]; Cruz, Mara Cristina Pessôa da [UNESP]; Berchielli, Telma Teresinha [UNESP] (Springer Nature, 2022)
The effects of sources of rumen undegradable protein (RUP) in diets on methane (CH4), nitrous oxide (N2O) and ammonia (NH3) emissions from the manure of feedlot-finished cattle were evaluated. We hypothesized that the use of different RUP sources in diets would reduce N loss via urine and contribute to reduced N2O, CH4 and NH3 emissions to the environment. Nellore cattle received different diets (18 animals/treatment), including soybean meal (SM, RDP source), by-pass soybean meal (BSM, RUP source) and corn gluten meal (CGM, RUP source). The protein source did not affect the N and C concentration in urine, C concentration in feces, and N balance (P > 0.05). The RUP sources resulted in a higher N2O emission than the RDP source (P = 0.030), while BSM resulted in a higher N2O emission than CGM (P = 0.038) (SM = 633, BSM = 2521, and CGM = 1153 g ha−2 N–N2O); however, there were no differences in CH4 and NH3 emission (P > 0.05). In conclusion, the use of RUP in diets did not affect N excretion of beef cattle or CH4 and NH3 emission from manure, but increased N2O emission from the manure.